Presenting Symptom as a Predictor of Clinical course in Juvenile Onset Recurrent Respiratory Papillomatosis. (17th December 2020) - Mudd, Pamela; Wikner, Emily; Rana, Md Sohel; Zalzal, George
Abstract : Objective/Hypothesis: Determine if the presentation of voice versus airway symptoms at the time of diagnosis of juvenile recurrent respiratory papillomatosis (JORRP) correlates with treatment and outcomes. Study Design: Original report, Retrospective review. Methods: Twenty year retrospective review of all patients with JORRP presenting at any time in treatment to a single tertiary children's hospital between 1997 and 2017. Results: Fifty‐four patients presented with a diagnosis of JORRP during the 20 year study period. Of these, 32 were female and 22 were male. African American children made up the majority of the patients (65%), with 19% identifying as Caucasian, 9% Hispanic, and 7% Asian. Fifteen of the children presented initially to the ENT clinic (87% with hoarseness), 12 to the emergency department (92% with airway concerns), 11 to the voice clinic, and the remaining 12 at outside hospitals or clinics and care were transferred. Voice symptoms, namely hoarseness, was the presenting symptom in 31 (57%), airway symptoms, namely respiratory distress or stridor was predominate in 17 (32%), and the presenting symptom was unknown in six cases (11%). Children presenting with airway symptoms were younger at presentation (median 2.1 years, range 0.38–8.77 years) than those presenting with voice symptoms (median 6.7 years, range 0.98–15.13 years), and after adjusting for age underwent a greater number of surgeries in the first year to control disease. Conclusions: Patients who present with airway symptoms present younger and have an increased number of surgeries in the first year compared to those presenting with voice complaints. Level of Evidence: 4 Laryngoscope, 131:1670–1675, 2021